Meningkatkan Keterampilan Siswa pada Mata Pelajaran IPAS melalui Model Student Facilitator and Explaining di Sekolah Dasar - Sitanggang, Raysyah Putri; Pratiwi, Indah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study aims to examine the enhancement of student skills in science learning through the application of the Student Facilitator and Explaining model in elementary education. Employing a classroom action research approach, the study was conducted in two cycles, each comprising stages of planning, implementation, observation, and reflection. If the targeted learning outcomes in the first cycle were not achieved, adjustments were made and continued into the second cycle. The results indicate that the implementation of this interactive learning model significantly improved students’ abilities, particularly in constructing diagrams or concept maps related to the photosynthesis process. Prior to the intervention, only 30% of students demonstrated sufficient competency. Following the first cycle, the average student performance increased to 80%, and in the second cycle, it further improved to 80.95%, reaching the "skilled" category. These findings suggest that the Student Facilitator and Explaining model effectively enhances student engagement and conceptual understanding in science education at the elementary level. Consequently, this approach can be considered a viable strategy for improving learning outcomes and fostering active participation among young learners.